2023
DOI: 10.3390/fishes8050252
|View full text |Cite
|
Sign up to set email alerts
|

Piscine orthoreovirus Genotype-1 (PRV-1) in Wild Pacific Salmon of British Columbia, Canada: 2011–2020

Abstract: Piscine orthoreovirus genotype 1 (PRV-1) is an endemic virus to the Northeastern Pacific that infects both wild and farmed salmon. To better understand PRV-1 prevalence and transmission pathways in the region, we targeted out-migrating juvenile Pacific Salmon in the Strait of Georgia and Johnstone Strait in British Columbia, Canada, for PRV-1 molecular screening with an emphasis on Chinook (Oncorhynchus tshawytscha) and Coho (Oncorhynchus kisutch) salmon. A total of 4031 individuals were screened for PRV-1 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…One major concern is pathogen release in rivers where juvenile salmonids may be infected since these may be particularly susceptible to infection and to develop disease with increased mortality. Previous studies have shown that wild juveniles in rivers in western Canada and Norway were infected with pathogens that may occur in salmon farming (Plarre et al., 2005; Turcotte et al., 2023). Our preliminary results from a study on salmonid juveniles show that PRV‐1 and PMCV infections occur in parr in Norwegian rivers (Madhun et al.…”
Section: Discussionmentioning
confidence: 99%
“…One major concern is pathogen release in rivers where juvenile salmonids may be infected since these may be particularly susceptible to infection and to develop disease with increased mortality. Previous studies have shown that wild juveniles in rivers in western Canada and Norway were infected with pathogens that may occur in salmon farming (Plarre et al., 2005; Turcotte et al., 2023). Our preliminary results from a study on salmonid juveniles show that PRV‐1 and PMCV infections occur in parr in Norwegian rivers (Madhun et al.…”
Section: Discussionmentioning
confidence: 99%